Non-linear analytical model for synchronous reluctance machine - Solak, Burak; Sapmaz, Tunahan; Oner, Yasemin (ELSEVIER, 2023)
This paper proposes an non-linear magnetic equivalent circuit (MEC) method for the synchronous reluctance machine (SynRM). The rotor geometry of the prototype machine is not simplified. In addition, the proposed MEC model can be used with different slot/pole combination or dimensions. While modeling SynRM, the non-linear effect and the leakage flux of the windings is taken into account. Due to the non-linear effect of the BH-curve, iterative algorithm process is used to find electromagnetic performances and magnetic permeability of non -linear reluctances. Finally, the proposed MEC is validated by both the finite element method (FEM) and experimental results to prove its accuracy and practicality.
Keywords: Analytical model; Magnetic equivalent circuit; Synchronous reluctance machines; HYBRID ANALYTICAL-MODEL; MAGNETIC-FIELD ANALYSIS; INDUCTION-MOTOR; FAULT-DETECTION; TORQUE; SATURATION; DESIGN; OPTIMIZATION; PERFORMANCE; Materials Science; Physics